Propriedades psicométricas da versão em português brasileiro da escala de comportamento impulsivo upps-p para crianças e adolescentes - Yuri de Castro Machado (2020)
Impulsivity is a factor that permeates various neuropsychiatric disorders, and its definition is widely discussed in the scientific literature. In an attempt to clarify the definitions of this phenomenon and better characterize the components related to impulsivity, the UPPS impulsivity scale was created. Initially, this scale assessed four parameters: negative urgency, lack of premeditation, lack of perseverance, and sensation seeking. Later, due to identifying that phenomena related to positive urgency were also present in impulsive individuals, a second version of the scale was created, including this parameter, called UPPS-P. Subsequently, there were adaptations, reducing the number of items for easier administration and creating a version for children and adolescents. The objective of this study is to translate and validate the UPPS-P scale for children and adolescents into Brazilian Portuguese. For this purpose, the translation and adaptation of UPPS-P were conducted in five stages. The first stage involved the translation of two independent versions of the original scale into Brazilian Portuguese. Subsequently, these two translations were merged, resolving discrepancies in words, meanings, or ambiguities. This initial Portuguese version was then back-translated into English by two independent evaluators, ensuring no semantic or idiomatic discrepancies caused by translation. After adjustments based on the observations from the previous step, the scale was reviewed by three experts from the fields of psychiatry, pediatrics, and psychology. Following these stages, the comprehension of the items was verified with 20 children aged 7 to 17, asking them if the items were clear enough to be answered. After this phase, the validation process began. Initially, the scale was filled out by 12 experts who analyzed whether the items were truly assessing what they aimed to measure. Only after this step, the UPPS-P scale was administered online to a population of 189 children and adolescents aged 7 to 17 from all regions of Brazil. The scale was re-administered to a group of 30 participants 4 months after the initial application. Half of this group was re-administered the scale online, while the other half was done through live video conferencing to assess the consistency of responses over time and across different administration methods. The application was conducted alongside the impulsivity scale, the Swanson, Nolan, and Pelham - Version IV (SNAP-IV) scale, the "Inventory of Childhood and Adolescence Behaviors" (ICIA) scale, and the Brazil Economic Classification Criteria. After data collection, the results were analyzed, revealing a strong correlation between the analyzed scales and good agreement with the original scale data, indicating that the Brazilian Portuguese version of the UPPS-P scale for children and adolescents is a reliable instrument for impulsivity analysis and is suitable for the Brazilian context.